Alternate Healthy Eating Index is Positively Associated with Cognitive Function Among Middle-Aged and Older Hispanics/Latinos in the HCHS/SOL. Issue 6 (24th February 2020) - Estrella, Mayra L; Durazo-Arvizu, Ramon A; Mattei, Josiemer; Mossavar-Rahmani, Yasmin; Perreira, Krista M; Siega-Riz, Anna Maria; Sotres-Alvarez, Daniela; González, Hector M; Gallo, Linda C; Daviglus, Martha L; Lamar, Melissa
ABSTRACT: Background: Diet quality may be an important area of focus for promoting cognitive health; however, the association between diet quality and cognitive function among Hispanics/Latinos remains largely unexamined. We hypothesized that a healthier diet quality will be associated with better cognitive function in middle-aged and older Hispanics/Latinos. Objective: The objective of this study was to examine associations between the Alternate Healthy Eating Index (AHEI-2010), a measure of diet quality, and cognitive function in middle-aged and older Hispanics/Latinos. Methods: Data from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) Visit 1 (2008–2011) were used ( n  = 8461; ages 45–74 y). Cognitive function was assessed with tests of verbal learning and memory, verbal fluency, and processing speed; a global cognition score was derived by summing the z scores of individual tests. Dietary intake was assessed via two 24-h recalls. Total AHEI-2010 score was categorized into quintiles (higher quintiles indicating healthier diet). Linear regression models were used to examine associations between AHEI-2010 quintiles and cognitive function adjusting for sociodemographic characteristics, daily energy intake, type 2 diabetes, smoking, and depressive symptoms. Results: Compared with the lowest quintile, in the second to fourth AHEI-2010 quintiles, global cognition scores were significantly higher by 0.28, 0.52, and 0.48 units ( P -trend = 0.042). In the second to fifth AHEI-2010 quintiles, verbal learning scores were significantly higher by 0.60, 0.62, 0.92, and 0.88 units, and verbal memory scores were higher by 0.33, 0.40, 0.52, and 0.46 units ( P -trend = 0.020 and 0.007, respectively). No associations were observed between the AHEI-2010 and verbal fluency or processing speed ( P -trend = 0.49 and 0.84, respectively). Among AHEI-2010 components, adequate consumption of vegetables, alcohol, and whole fruits were each associated with better cognitive function. Conclusions: An overall healthier diet quality was associated with better global cognition, verbal learning, and verbal memory in middle-aged and older Hispanics/Latinos.